Self-leadership change project: the continuation of an ongoing experiential program. Issue 3 (13th March 2017) - Phillips, James I.; Kern, Dave; Tewari, Jitendra; Jones, Kenneth E.; Beemraj, Eshwar Prasad; Ettigi, Chaitra Ashok
Abstract : Purpose: The self-leadership change project (SLCP) is an ongoing program for senior level students at a regional university designed to provide hands-on experience in building self-management skills, which is considered a pre-requisite by many leaders and scholars (e.g. Drucker, 1996; Schaetti et al., 2008). The paper aims to discuss this issue. Design/methodology/approach: Participants (479 undergraduate business students in 26 different classes with two different professors) had from 10 to 16 weeks to complete their SLCP project. A survey to collect the data for this study were provided as a voluntary option to participants who wished to report their SLCP project results. Findings: A majority of students participating in the projects reported achieving change in targeted behavior, with intentions to continue to utilize the SLCP approach for future "projects." Additionally, students who successfully completed a SLCP reported that observers noted change in others as a result of the project. Students who received positive feedback from observers reported that they were likely to engage in a self-leadership project in the future. Research limitations/implications: The data used in the analysis are exclusively self-reported information. The survey and results do not tie to previous studies that measure individuals' aptitude for self-leadership as an indicator of success and development of self-leadership capabilities. This study offers little in the way of acknowledging or determining the sustainability of changes desired. Practical implications: The results fully supported the idea that self-leaders influence others. Social implications: This study providing support for the concept that external leadership begins with self-leadership. Successful self-leadership change prepares an individual for external leadership roles in organizations and society. Originality/value: The relationship noted in "Practical implications" above has been suggested in the literature, but there have been few studies covering this relationship.